Covid-19 and the Experience of the Elderly Students: The case of the University Program for the Elderly of the Nuevo León Autonomous University, México - Silva Morín, Luz Amparo; Escalera Silva, Luz Alejandra; López Estrada, Raúl Eduardo (North American Business Press, 2021)
Covid-19 and the digital experience in education for older adults are analyzed. To this end, we examine those elements that could favor the continuity of distance programs; in this case the UANL University Program for the Elderly was taken as a case study. The UANL University for the Elderly Program was taken as a case study. The conclusion highlights that the digital experience during the pandemic was successful, however in considering a continuity of the program, risk factors associated with environmental factors, technical factors: education and information technology, and interest should be taken into account. in classroom education.